Mismatch repair proteins play a role in ATR activation upon temozolomide treatment in MGMT-methylated glioblastoma - Ganesa, Sachita; Sule, Amrita; Sundaram, Ranjini K.; Bindra, Ranjit S. (Scientific reports, 2022)
The methylation status of the O 6 -methylguanine methyltransferase ( MGMT ) gene promoter has been widely accepted as a prognostic biomarker for treatment with the alkylator, temozolomide (TMZ). In the absence of promoter methylation, the MGMT enzyme removes O 6 -methylguanine (O 6 -meG) lesions. In the setting of MGMT -promoter methylation (MGMT-), the O 6 -meG lesion activates the mismatch repair (MMR) pathway which functions to remove the damage. Our group reported that loss of MGMT expression via MGMT promoter silencing modulates activation of ataxia telangiectasia and RAD3 related protein (ATR) in response to TMZ treatment, which is associated with synergistic tumor-cell killing. Whether or not MMR proteins are involved in ATR activation in MGMT-cells upon alkylation damage remains poorly understood. To investigate the function of MMR in ATR activation, we created isogenic cell lines with knockdowns of the individual human MMR proteins MutS homolog 2 (MSH2), MutS homolog 6 (MSH6), MutS homolog 3 (MSH3), MutL homolog 1 (MLH1), and PMS1 homolog 2 (PMS2). Here, we demonstrate that MSH2, MSH6, MLH1 and PMS2, specifically, are involved in the activation of the ATR axis after TMZ exposure, whereas MSH3 is likely not. This study elucidates a potential mechanistic understanding of how the MMR system is involved in ATR activation by TMZ in glioblastoma cells, which is important for targeting MMR-mutated cancers.